Suficiência de ativos garantidores e provisões técnicas em operadoras de plano de saúde - Duarte, Sérgio de Melo (2015)
In the 1990s there were several changes in the healthcare industry in Brazil. One of the most important was the change of the Law regulating operators plans and health insurance (OPS). The creation of the National Health Agency (ANS), as normative organ and inspector of the health sector, enabled the structuring of health care with respect to the segment of health insurance. Focusing on the sustainability of this segment, characterized by high care costs, the ANS, through the Normative Resolution No. 209/2009 established constitution criteria of technical provisions and the Resolutions Nos. 159/2007 and 227/2010 determined constitution criteria of collateral assets needed for ballasting of any obligations under these provisions. It occurs even if such assets are not always sufficient to this ballasting in full. Under this focus, this research has as main objective to investigate what the behavior of economic and financial indicators, comparatively, the OPS with and without sufficiency of collateral assets. As to the objectives, it is a descriptive research. As for the problem of approach, the study is quantitative. As for the procedures, we used bibliographical and documentary research, the main sources doctrine and legislation on the subject. Data for the analysis were collected from the National Health Agency's website, referring to the three-year period 2011/2013. To analyze the results, we used the SPSS statistical tool for calculating the average of test and measurement of the correlation index between the variables of the research. The study indicated that, although the amount of operators with sufficiency of collateral assets have always been superior to OPS without sufficiency, there was a regression trend of this group in the participation of the sample, due to the sharp increase in technical provisions. It therefore committed the financial indicators of the OPS. The average test allows us to state that the OPS with and without sufficiency of collateral assets are statistically different.